BOHUMIL POLAN AWARD (THIS TIME) IN THE SIGN OF A (POETIC) EXPERIMENT - Harák, Ivo (Bohemica Olomucensia, 2020)
In his study, Ivo Harák deals with location of the fine artist Jan Jelínek's writing. Harák sees it in context of the West Czech region but he also considers Jelínek's reach beyond regions. Harák analysis both of Jelínek's published books of poems pointing out the roots and significant features of Jelínek's writing.
Keywords: Bohumil Polan Award; poetic experiment; West Bohemia